2023
DOI: 10.53391/mmnsa.1274004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Influenza A disease dynamics under Caputo-Fabrizio fractional derivative with distinct contact rates

Abstract: The objective of this manuscript is to present a novel approach to modeling influenza A disease dynamics by incorporating the Caputo-Fabrizio (CF) fractional derivative operator into the model. Particularly distinct contact rates between exposed and infected individuals are taken into account in the model under study, and the fractional derivative concept is explored with respect to this component. We demonstrate the existence and uniqueness of the solution and obtain the series solution for all compartments u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Here, we utilized a recent and effective numerical scheme introduced by [41] to gain insight into the solution trajectories. For a detailed analysis of this method's convergence, accuracy, and stability, please refer to [41,42]. In Table 4, we provided the numerical values of the parameters used to find the proposed model's numerical simulations.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Here, we utilized a recent and effective numerical scheme introduced by [41] to gain insight into the solution trajectories. For a detailed analysis of this method's convergence, accuracy, and stability, please refer to [41,42]. In Table 4, we provided the numerical values of the parameters used to find the proposed model's numerical simulations.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…There are many mathematical modeling studies in the literature that examine interactions through compartments by using FODEs. For some of these, see [29,30]. Employees who are exposed to mobbing in a workplace always interact with other employees and employees who practice mobbing.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that the fractional model provided helpful information on TB and a better way to view the spread of the disease. There have been so many studies on the use of fractional derivatives in modeling infectious diseases as can be seen in [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Models that have utilized fractional derivatives in non-disease modeling can be seen in [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%